THEORETICAL FEATURES OF THE FORMATION AND DEVELOPMENT OF THE SYSTEM OF PHYSICAL EDUCATION IN SECONDARY SCHOOLS (Scientific journal of the Fergana State University, 2023)
This direction of research is promising, since the addition of compulsory classes according to the physical education program with physical culture and wellness work in extracurricular form does not cause controversy among most researchers. It should be recognized that a number of practitioners and researchers are making active and sometimes successful attempts to prove that a methodically properly organized system of compulsory education in the education system can be an effective direction in improving the physical fitness of young people studying. At the same time, some categories of researchers believe that the main way is to translate basic forms of physical training based on traditional orientation training to the fullest possible use of the effect of physical exercises. This makes it possible to conduct physical education classes in conditions of high motor intensity and high heart rate, which ultimately leads to an expansion of the possibilities of physical adaptation of an organism with a large size and intensity, and a decrease in the morbidity of the studied contingent.